DIPG-22. Modifying the tumor microenvironment with a TIM-3 monoclonal antibody as a therapeutic strategy for DIPGs. (3rd June 2022) - Ausejo-Mauleon, Iker; Labiano, Sara; De la Nava, Daniel; Garcia-Moure, Marc; Laspidea, Virginia; Becher, Oren J; Jiang, Li; Filbin, Mariella G; Pastor, Fernando; Alonso, Marta M
Abstract: Diffuse Midline Glioma, encompassing Diffuse Intrinsic Pontine Gliomas (DIPGs), are the most aggressive pediatric brain tumors. Their meager survival has not changed despite the combination of radiotherapy with targeted therapies emphasizing the urgent need for effective treatments. TIM-3 (HAVCR2) is a member of the T-cell immunoglobulin and mucin domain protein family. It is expressed on multiple immune cell types, including T cells, NK cells, myeloid populations, and microglia, regulating adaptive and innate immunity. In silico assessment of TIM-3 expression in DIPG datasets showed a robust expression of this gene. Single-cell sequencing analyses of DIPG biopsies uncover TIM-3 expression, especially in microglia. In vivo efficacy studies showed that treatment with AbTIM-3 significantly increased overall survival in two DIPG immunocompetent orthotopic models, led to long-term survivors (50%), and showed immune memory. TIM-3 treatment led to a significant increase in the tumor microenvironment of microglia, granulocytes, NK, and CD8+ cells and higher levels of IFNγ, GrzB and TNFα corresponding with an NK and T-cell activate phenotypes. Interestingly, there was a decrease in the Treg population which causes an increase in the pro-inflammatory CD8/Treg ratio. CD4, CD8 or NK cell depletion leads to a significant but not a total loss of treatment efficacy. CD4+ and CD8+ cells were aumented in treated draining lymph nodes and expressed higher amounts of pro-inflamattory cytokines than control-mice. Population analysis and depletion experiments demonstrated the relevance of NK, CD4, CD8 and myeloid populations in the response to anti-TIM-3 therapy. Interestingly, the depletion of the different immune populations combined or using immunodeficient Rag2 mice, did not completely abrogate the treatment efficacy. These results suggest the concurrence of an additional mechanism of action that together with the immune response leads to a robust anti-DIPG effect. In conclusion, these data demonstrate that TIM-3 is a potential target for the treatment of DIPG.